An Examination of High School Personnel Prepare Students with Disabilities to Self-advocate for Favorable Post High School Outcomes. - Martin, Barbara N; Wittmeyer-Gruber, Leigh (Advances in Social Sciences Research Journal, 2018)
This paper explored the perceptions of special education staff and college students with disabilities about self-advocacy instruction provided in high schools. Data revealed differing perceptions about the level of self-advocacy instruction that students with disabilities receive while in high school between teachers and students. The implications for this research and practice include opportunities that high schools must have to teach students with disabilities self-advocacy skills to prepare them for post-school success.